GW24-e0505 Direct comparison of SW-CG-HYPR and conventional SR-Turbo-FLASH myocardial perfusion MRI for detection of coronary artery disease. (1st October 2013) - Jun, Yang; Ma, Heng; Jing, Yanyan; Liu, Jing; Ge, Lan; Li, Debiao
Abstract : Objectives: Sliding-window conjugate-gradient highly constrained back-projection reconstruction (SW-CG-HYPR) myocardial perfusion MRI allows increased spatial coverage, improved temporal and spatial resolution and signal-to-noise ratio compared with the conventional SR-Turbo-FLASH. The diagnostic accuracy of myocardial perfusion MRI with SW-CG-HYPR for detecting coronary artery disease (CAD) has not been directly compared to that with conventional SR-Turbo-FLASH. The purpose of the work was to prospectively compare the diagnostic value of SW-CG-HYPR and conventional SR-Turbo-FLASH for myocardial perfusion MRI in patients with suspected CAD. Methods: Thirtyconsecutivepatients with suspected CAD who were scheduled for coronary angiography underwent myocardial perfusion MRI with both SW-CG-HYPR and SR-Turbo-FLASH in random order at 3.0 T. Perfusion defects were interpreted visually by 2 blinded observers and were correlated to x-ray angiographic stenoses ≥ 50%. Receiver-operating characteristic (ROC) curve analysis was used to compare the diagnostic performance of the two imaging techniques. Results: In the per-patient analysis, SW-CG-HYPR provided a higher sensitivity (94% vs. 89%), specificity (83% vs. 75%) and diagnostic accuracy (90% vs. 83%) for detection of CAD than SR-Turbo-FLASH. In the per-vessel analysis, the diagnostic performance of SW-CG-HYPR was significantly greater than that of SR-Turbo-FLASH for the overall detection of CAD (area under ROC curve: 0.96 ± 0.02 vs. 0.90 ± 0.03, respectively; p < 0.05). Conclusions: SW-CG-HYPR myocardial perfusion MRI has higher diagnostic accuracy than conventional SR-Turbo-FLASH for detection CAD.